School Administrator’s skills Affect to The 21st Century Skills Of Teachers Under Phranakhon Si Ayutthaya Primary Educational Service Area Office 2 - Chaisiribavorn, Tanyavat; Montaisong, Teerawat (Mahachula Academic Journal, 2024)
The purposes of this research are (1) to study school administrators’ skills of Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 2 (2) to study the 21st century teachers’ skills in in Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 2 (3) to study the school administrators’ skills affect the 21st century teachers’ skills of the Office of Phra Nakhon Si Ayutthaya Primary Educational Service Area 2 and the samples in this research were 285 teachers. The questionnaire about the school administrators’ skills gets the confidence value was 0.98. The questionnaire about the 21st Century teachers’ skills gets the confidence value was 0.99. The Statistics which used in data analysis were mean, standard deviation. Pearson’s correlation coefficient (r) and multiple regression analysis by the enter method. The research findings were as follows (1) the school administrators’ skill of the Office of Phra Nakhon Si Ayutthaya Primary Educational Service Area 2 in the overall level was at high level. The highest aspect was communication skill, followed by technology digital skill and the lowest aspect was knowing and thinking skill (2) the 21st century teachers’ skills of the Office of Phra Nakhon Si Ayutthaya Primary Educational Service Area 2 in the overall level was at a high level. The highest aspect was learning management skills followed by the professional learning development skill and the lowest aspect were the technology skill, respectively. (3) The school administrators’ skills had a positive correlation with the 21st century teachers’ skills in the Office of Phra Nakhon Si Ayutthaya Primary Educational Service Area 2 in overall is moderate by statistically significant at .01 (4) School administrators’ skills affect to the 21st skills of teachers under Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 2 which the overall was moderate level. The statistical significance at the .05 level consisted of cognitive skills, technical skills, human skills, thinking skills, communication skills and technology digital was 52.10 percent.